Analisis Kelayakan Finansial Ternak Ayam Pedaging Usaha Peternakan D2 di Perbaungan Sumatra Utara - Nadiah Nadiah; Puja Aulia Amanda; Yuyun Ulandari; Josian Amanda Ginting; Kiagus Muhammad Zain Basriwijaya (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
D2 Farm business is a business engaged in the production of broilers. This study aims to determine the level of income and financial feasibility of the D2 farm broiler business based on the criteria (R / C Ratio) and (B / C Ratio) in one year of production, which was carried out in November 2024. The location of this research was determined purposively (Purposive Sampling). The results showed that the income received by the D2 farm broiler business in one year was Rp. 486,606,603, the R / C Ratio was 5.23 and the results of the B / C Ratio calculation were 3.31, which means that the D2 farm broiler business is feasible to develop.